The impact of the costs of the package tour on determining the promotional price of tourism services - Mohammed Bendjaballah (Dirassat Journal Economic Issue, 2020)
The study aimed to try to get acquainted to the cost branch in the tourism services, which is a major factor in determining its price, especially what relates to the package tour, which is an integrated set of tourism services whose its cost less with its greatly varied. This diversification leads to the revitalization of tourism and increases its competitiveness  and then decreases its prices as a result.The study also included a simulation for estimating the costs of the package tour  based on data attributed to methods that can calculate the cost of the package tour  and its application on some hotels belonging to four cities for comparison , namely , Algiers , Casablanca , Tunis, Cairo , so the last three cities are capitals of countries Its tourism industry is more than Algeria, so the study ends with an estimate of the cost of the package tour , which is the basis for setting prices.As a result, this study concluded a set of results and recommendations. the foremost, Algeria has capabilities that enable it to exploit the tourism activity based on harnessing the infrastructure, thus reducing costs and then reducing prices due to competition in this sector.